Simulation and Experimental Analysis of Influence of Inlet Flow on Heavy Hydrostatic Bearing Temperature Field - Qin Zhang, Yan; Wei Li, Wei; Guo Fan, Li; Li, Rui; Peng Shao, Jun (Asian Journal of Chemistry, 2014)
A multiple pad round guide was taken to solve the friction failure problem caused by the increase of the local temperature. The relationship between temperature and oil viscosity was systematically studied and an equation was established. Moreover, the fluid temperature field inside the hydrostatic bearing with a rotation speed of 6 rpm was simulated at various flows and viscosities based on finite volume method. The influences of the inlet flow on the temperature of the clearance oil film were also studied. The results show that the shear flux plays an important role at low flux, while the stress difference flux on the clearance oil pad acts a vital part at high flux. In addition, the approximate high temperature area was searched out through numerical simulations of the oil film temperature field of the hydrostatic thrust bearing and then the effective temperature control was found out.